2019
DOI: 10.3389/fendo.2019.00538
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dependent Dysregulation of Hepatic Glucose Production in Lean Type 2 Diabetic Rats

Abstract: We have characterized a lean type 2 diabetic rat model by gestational low protein programming. We aimed to identify if the regulation of hepatic glucose production (HGP) via gluconeogenesis and glycogenolysis is affected and if there are any sex differences. Fasting (6–7 months old) type 2 diabetic rats received 2 H 2 O followed by a primed constant rate infusion of [6,6- 2 H 2 ] glucose. Blood samples were drawn during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
1
5
1
Order By: Relevance
“…Data from other laboratories show that a gestational LP diet caused changes in hepatic gene expression by various mechanisms linked to glucose metabolism [ 10 , 11 , 12 , 13 ]. Similarly, our previous study in LP-programmed females showed impaired hepatic glucose metabolism [ 2 , 14 , 15 , 16 , 17 ]. However, the molecular mechanism leading to defects in hepatic glucose metabolism and its relationship to mitochondrial abnormalities in the liver is not well studied.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Data from other laboratories show that a gestational LP diet caused changes in hepatic gene expression by various mechanisms linked to glucose metabolism [ 10 , 11 , 12 , 13 ]. Similarly, our previous study in LP-programmed females showed impaired hepatic glucose metabolism [ 2 , 14 , 15 , 16 , 17 ]. However, the molecular mechanism leading to defects in hepatic glucose metabolism and its relationship to mitochondrial abnormalities in the liver is not well studied.…”
Section: Introductionsupporting
confidence: 68%
“…Such developmental reprogramming of the offspring often leads to various metabolic diseases later in life, including insulin resistance and type 2 diabetes (T2D). It is known that maternal dietary protein is important for fetal liver development, and an in utero low-protein diet (LP) causes insulin resistance and impaired liver function in offspring [ 2 ]. As one of the major hubs of metabolism, the liver regulates glucose metabolism in response to the changing nutrient availability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They developed progressively worsening glucose intolerance and insulin resistance with advancing age without any increase in body weight, body mass index, or fat content when compared with controls [ 25 , 28 ]. We also showed that gestational LP diet caused T2D in adult offspring with different signaling mechanisms in males and females [ 25 , 26 , 27 , 29 , 30 ]. Our studies in females showed that impaired glucose homeostasis is caused due to a defect in the insulin signaling cascade, which regulates glycogen synthesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies in females showed that impaired glucose homeostasis is caused due to a defect in the insulin signaling cascade, which regulates glycogen synthesis [ 26 ]. Further, we also showed that LP programming affects hepatic glucose production via both gluconeogenesis and glycogenolysis in a sex-dependent manner with greater dysregulation in females when compared to males [ 29 ]. The present study aims to investigate the role of mitochondrial health in the skeletal muscle in LP-programmed T2D female offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is vascular catheterization less technically challenging in the rat compared to the mouse, but mice require infusion of donor blood to replace erythrocytes and sustain hematocrit during clamping procedures, which results in larger colony number and more complex experimental design (137). Independently of rodent model choice, however, blood glucose assessments must take into consideration; strain (40,139), age (140,141), sex (142)(143)(144), fasting length (137,145) and husbandry (146)(147)(148) as all of these parameters differentially impact glucose homeostasis and the translatability of each model to human physiology (discussed in detail in 7,9). Nonmammalian species, while having critical distinctions in their mechanisms of glucose homeostasis, particularly with respect to the brain, offer unique opportunities afforded by their genetic tractability, lower cost, and fecundity.…”
Section: Resultsmentioning
confidence: 99%